Academic identity of university students A field study at the Faculty of Psychology and Educational Sciences, University of Constantine (02 (مجلة الواحات للبحوث والدراسات, 2026)
The study aimed to know the academic identity of the university student. The number of sample members reached (82 students) from the Faculty of Psychology and Educational Sciences at the University of Constantine -02-. To achieve the objectives of the study, the academic identity scale of (DeCandia) was applied.Decandia, 2014), by following the descriptive approach, the results of the study showed that the level of academic identity among university students ranged between average and high, the level of orientation towards the future among most university students was high, the level of self-efficacy among most university students was average, the level of confidence in academic abilities among most university students was high, and the level of perseverance among most university students was average.